2001
DOI: 10.1016/s1532-0456(01)00260-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Ca inhibits waterborne Cd uptake in Cd-exposed rainbow trout, Oncorhynchus mykiss

Abstract: The effects of chronic exposure to waterborne Cd and elevated dietary Ca, alone and in combination, were examined Ž . w in juvenile rainbow trout, Oncorhynchus mykiss. Fish were chronically exposed to 0.05 control or 2.56 grl Cd as Ž . x Ž . Ž Cd NO и 4H O and were fed 2% body massrday of control 29.6 mg Carg or Ca-supplemented trout food 52.8 mg uptake from water into the gill and induced hypocalcemia in the plasma on day 40. Waterborne Cd also induced an elevated Ca concentration on day 20 in the gill tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Similar results were found in tilapia (Oreochromis niloticus) fed diets containing Cd from 5 to 100 µg.g -1 dry food, in which Cd content in feces were ≤ 279 µg.g -1 (Nogami et al, 2000). Although high concentrations of Ca 2+ in either the water or the diet clearly have ameliorative effects on waterborne Cd toxicity in fish (e.g., Hollis et al, 2000;Zohouri et al, 2001;Baldisserotto et al, 2005), it is unclear whether the low water Ca 2+ concentration in the holding tanks (~10 µmol.L -1 ) contributed to amplify the dietary Cd accumulation in tambaqui. The sensitivity of tambaqui to waterborne Cd has been reported in a previous study (Matsuo et al, 2005), and the effect of soft water on dietary Cd accumulation still needs further investigation.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were found in tilapia (Oreochromis niloticus) fed diets containing Cd from 5 to 100 µg.g -1 dry food, in which Cd content in feces were ≤ 279 µg.g -1 (Nogami et al, 2000). Although high concentrations of Ca 2+ in either the water or the diet clearly have ameliorative effects on waterborne Cd toxicity in fish (e.g., Hollis et al, 2000;Zohouri et al, 2001;Baldisserotto et al, 2005), it is unclear whether the low water Ca 2+ concentration in the holding tanks (~10 µmol.L -1 ) contributed to amplify the dietary Cd accumulation in tambaqui. The sensitivity of tambaqui to waterborne Cd has been reported in a previous study (Matsuo et al, 2005), and the effect of soft water on dietary Cd accumulation still needs further investigation.…”
Section: Discussionsupporting
confidence: 69%
“…In agreement to our finding, previous finding from Muramoto (1981) has also showed that Cd ?2 could influence bone metabolism and may disturb its structure and causes hypocalcaemia. Zohouri et al (2001) showed that waterborne Cd ?2 induce hypocalcaemia in rainbow trout fish. Hypocalcaemia was also reported as a most sensitive effect of Cd ?2 toxicity in common carp during Cd ?2 exposure (Hans et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Muramoto (1981) reported the appearance of bone problem and specifically Ca deficiency in common carp following Cd ?2 exposure. Investigations by many other researchers have also confirmed that Cd ?2 induced hypocalcaemia in fish (Haux et al 1988;Zohouri et al 2001;Hans et al 2006) and has altered the serum ALP level (Sastry and Subhadra 1985;Gill et al 1991;Al Attar 2005;Velmurugan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is an interesting parallel here to cadmium metabolism, which is thought to be taken up across the gill via apical Ca 2+ channels in the ionocyte (Verbost et al, 1989). Recently, Zohouri et al (2001) reported that elevated dietary Ca 2+ reduced but did not eliminate branchial cadmium uptake in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%